Case Report of Speech and Ambulation Ability After Five Years Therapy in a Six-Year-Old Boy with Habilitation Sixth Lumbar Spina Bifida with Meningocele Post Resection and Hydrocephalus Post VP Shunt - Naela Munawaroh; Lisa Nurhasanah; Rahmi Isma AP (Indonesian Journal of Physical Medicine & Rehabilitation, 2022)
ABSTRACT Introduction: Spina bifida, a congenital spinal cord injury, is a complex disability that results from a failure of the caudal neural tube to fuse early in embryonic development. Spina bifida affects about 300.000 newborns each year worldwide. Hydrocephalus is common in children with spina bifida, developing in 80% to 90% of children with myelomeningocele. Anatomical abnormalities in which the myelomeningocele sac occurs is associated with neurological, motor and sensory deficits. They showimpaired speech and ambulation.Case presentation: We report a six-year-old boy was taken to the hospital by his parents because he could not stand and walk since he was born. At birth there was a lump on the lower back, and the patient also had hydrocephalus, then surgery had been performed. The patient was diagnosed with sixth lumbar spina bifida and hydrocephalus with meningocele. He had some delay in gross motor, fine motor and language development. The patient had history of seizures. He received trunk control exercise, pelvic stabilityexercise, positioning and handling, coordination exercises and fine motor skills to increase independence in activities of daily life. The patient obtained 4 years exercises of speaking, comprehension, vocabulary and articulation. The child also received attention and concentration enhancement exercises.Conclusion: A patient with spina bifida requires a lifelong commitment by the patient, family, and the health care personnel involved in the treatment. The medical goal is to maintain stable neurological functioning throughout the patient’s lifetime. The wide range of extensive speech and ambulation impairments and long-term disabilities in patients with spina bifida present a considerable challenge to the management of these patients.Keywords: ambulation, hydrocephalus, meningocele, speech, spina bifida